Colon cleansing protocol in children: research conditions vs. clinical practice - Elitsur, Yoram; Balfaqih, Yaslam; Preston, Deborah (Endoscopy International Open, 2018)
Background and study aims Colon preparation rates are the limiting factor for a successful diagnostic colonoscopy in children. Different colon cleansing protocols have been published for use in children. Unfortunately, the applicability of those published research protocols has not been formally evaluated in routine clinical practice. We investigated the success rate of our previously published colon cleansing protocol as utilized in our clinical practice.Patients and methods This was a retrospective study. In the clinical practice, the colon cleansing protocol included PEG-3350 at a dose of 2 g/kg/day plus Dulcolax (Bisacodyl, Boehringer Ingelheim, TX USA) 5 mg/day for 2 days. Adequate colon preparation was graded between 1 – 5, as previously described, and grade ≥ 4.0 was considered an adequate preparation. Patients were instructed to complete a questionnaire that included PEG-3350 dose, number of stools per day, consistency of each stool, and side effects (vomiting, abdominal pain). Clinical and endoscopic results were compared between the protocol under research conditions and routine practice.Results The success rate of the colon preparation in our clinical practice was similar to the results observed under our research protocol (75 % vs. 73.6 %). Moreover, the total number of stools, stool consistency, and the intubation rate of the terminal ileum were also similar. We concluded, that in our experience, the colon cleansing protocol used under research conditions was effective and appropriate for use in routine clinical practice.Conclusion We recommend testing each new protocol under the routine conditions of clinical practice to confirm its applicability for general practitioners.